2019
DOI: 10.1016/j.ejca.2019.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of survival with second-line therapy in biliary tract cancer: Actualisation of the AGEO CT2BIL cohort and European multicentre validations

Abstract: Background: The benefit of second-line chemotherapy (L2) over standard first-line (L1) gemcitabine plus cisplatin (GEMCIS) or oxaliplatin (GEMOX) chemotherapy in advanced biliary tract cancer (aBTC) is unclear. Our aim was to identify and validate prognostic factors for overall survival (OS) with L2 in aBTC to guide clinical decisions in this setting. Methods: We performed a retrospective analysis of four prospective patient cohorts: a development cohort (28 French centres) and three validation cohorts from It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 23 publications
0
42
0
3
Order By: Relevance
“…Additionally, previous surgical therapy can rather be seen as a surrogate marker for relapse or progressive disease, rather than a real prognostic factor for survival. Interestingly, a predictive model based on 405 patients with biliary tract cancer revealed improved survival of patients who had undergone surgical resection of the primary tumor [24]. However, it has to be noted that this cohort included patients with various biliary tract cancers, including extrahepatic manifestation, in whom an R0 resection can be achieved much more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous surgical therapy can rather be seen as a surrogate marker for relapse or progressive disease, rather than a real prognostic factor for survival. Interestingly, a predictive model based on 405 patients with biliary tract cancer revealed improved survival of patients who had undergone surgical resection of the primary tumor [24]. However, it has to be noted that this cohort included patients with various biliary tract cancers, including extrahepatic manifestation, in whom an R0 resection can be achieved much more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we previously showed that all patients with aBTC do not benefit from L2 administration and that the CT2BIL score (mainly driven by ECOG PS) may be useful in this setting. 7 In this article, our results suggest that FP monotherapy is as active as FP doublets in aBTC in L2, regardless of the patient PS and platinum sensitivity status, and could be a therapeutic option in this setting. This would warrant further prospective evaluation in randomized controlled trials.…”
Section: Discussionmentioning
confidence: 69%
“…7 We also identified absence of primary tumor resection, L1 discontinuation for progression, presence of peritoneal carcinomatosis, and high carbohydrate antigen 19-9 (CA19-9) serum level as other independent prognostic biomarkers for OS in this setting. 7 Second-line therapies for aBTC are as well heterogeneous, with no high-level prospective evidence available until recently. 8,9 In routine clinical practice, most patients receive fluoropyrimidine (FP, ie, intravenous 5-fluorouracil [5FU] or oral capecitabine) in monotherapy or combined with platinum or irinotecan, based on retrospective cohorts or small single-arm phase II studies.…”
mentioning
confidence: 81%
See 2 more Smart Citations